2023
DOI: 10.1159/000533991
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Atezolizumab/Bevacizumab in Patients with Hepatocellular Carcinoma and Impaired Liver Function: A Systematic Review and Meta-Analysis

Andrea Pasta,
Francesco Calabrese,
Ariel Jaffe
et al.

Abstract: BACKGROUND: Safety and outcome of atezolizumab/bevacizumab in Child-Pugh B patients with hepatocellular carcinoma (HCC) have not been completely characterized. OBJECTIVES: In this study we aimed at addressing safety and efficacy of atezolizumab/bevacizumab in Child-Pugh B patients by reviewing the available data and analysing them by meta-analysis. METHOD: We compared the safety and efficacy of atezolizumab/becavizumab treatment in patients with unresectable HCC and various degrees of liver dysfunction. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…14 Unfortunately,however, theauthorsdidnotreportoverallsurvivalfiguresinthesubsetsof intermediate-stagepatientswheresystemictreatment,ratherthan TACE,maymakethedifferencesuchasChild-PughclassBpatients andthosewithanalbumin-bilirubingrade ≥2,whereprogression-free survivalwasnotdifferentbetweenthetwotreatments,andwhere overallsurvivalwithsystemictreatmentisparticularlygrim. 15,16 Fromthepatientperspective,whendealingwiththerapyofan advancedcancerwithalowlikelihoodofdefinitecure,asthepopulation included in this study, the main questions are whether the proposedtreatmentwillhelpthemlivelongerandwhetherthiswill becompatiblewithagoodqualityoflife. 16 Thefirstpieceofinformationwecangleanfromthereal-worldstudyofTadaetal.isthat, even in patients with unfavourable liver-related and oncological features, treatment with either lenvatinib or atezolizumab/bevacizumabisassociatedwithoverallsurvivalfiguresthataremeaningfully longer than those reported in well-selected patients enrolled ©2023JohnWiley&SonsA/S.PublishedbyJohnWiley&SonsLtd.…”
Section: May We Actually Help Clinicians Select the Best Systemic Tre...mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Unfortunately,however, theauthorsdidnotreportoverallsurvivalfiguresinthesubsetsof intermediate-stagepatientswheresystemictreatment,ratherthan TACE,maymakethedifferencesuchasChild-PughclassBpatients andthosewithanalbumin-bilirubingrade ≥2,whereprogression-free survivalwasnotdifferentbetweenthetwotreatments,andwhere overallsurvivalwithsystemictreatmentisparticularlygrim. 15,16 Fromthepatientperspective,whendealingwiththerapyofan advancedcancerwithalowlikelihoodofdefinitecure,asthepopulation included in this study, the main questions are whether the proposedtreatmentwillhelpthemlivelongerandwhetherthiswill becompatiblewithagoodqualityoflife. 16 Thefirstpieceofinformationwecangleanfromthereal-worldstudyofTadaetal.isthat, even in patients with unfavourable liver-related and oncological features, treatment with either lenvatinib or atezolizumab/bevacizumabisassociatedwithoverallsurvivalfiguresthataremeaningfully longer than those reported in well-selected patients enrolled ©2023JohnWiley&SonsA/S.PublishedbyJohnWiley&SonsLtd.…”
Section: May We Actually Help Clinicians Select the Best Systemic Tre...mentioning
confidence: 99%
“…Interestingly, the latest American Association for the Study of Liver Diseases guidance on HCC management also defines a number of factors that contribute to unsuitability for trans‐arterial treatments 14 . Unfortunately, however, the authors did not report overall survival figures in the subsets of intermediate‐stage patients where systemic treatment, rather than TACE, may make the difference such as Child‐Pugh class B patients and those with an albumin‐bilirubin grade ≥2, where progression‐free survival was not different between the two treatments, and where overall survival with systemic treatment is particularly grim 15,16 …”
mentioning
confidence: 99%
“…The ALBI grade obviates the subjective assessment of parameters of the Child-Pugh classification, such as ascites and encephalopathy, and proved to be able to identify the subclasses of patients who may not derive a substantial survival benefit from various treatments, including surgery and loco-regional therapies, thus representing a valuable decision-making aid in clinical practice 16 . Noteworthy, the ALBI grade also helps stratify patients receiving systemic treatment: a subanalysis of the atezolizumab/bevacizumab registration study has shown that patients with an ALBI grade 1 benefit most from atezolizumab/bevacizumab compared to sorafenib (overall survival HR ALBI grade 1: 0.50, 95% CI: 0.35–0.72; ALBI grade 2: 0.92, 95% CI: 0.66–1.29), while a recent meta-analysis of real-world studies showed that patients with an ALBI grade >2 treated with atezolizumab/bevacizumab have a dismal prognosis as compared to those with lower ALBI grades (overall survival: 8.3±11.4 vs. 3.3 ± 5.0 months) 17,18 …”
Section: Impact Of Liver Function and Portal Hypertension On Therapeu...mentioning
confidence: 99%
“…[16] Noteworthy, the ALBI grade also helps stratify patients receiving systemic treatment: a subanalysis of the atezolizumab/bevacizumab registration study has shown that patients with an ALBI grade 1 benefit most from atezolizumab/bevacizumab compared to sorafenib (overall survival HR ALBI grade 1: 0.50, 95% CI: 0.35-0.72; ALBI grade 2: 0.92, 95% CI: 0.66-1.29), while a recent meta-analysis of real-world studies showed that patients with an ALBI grade > 2 treated with atezolizumab/bevacizumab have a dismal prognosis as compared to those with lower ALBI grades (overall survival: 8.3 ± 11.4 vs. 3.3 ± 5.0 months). [17,18] Portal hypertension is another relevant clinical issue that needs to be adequately assessed when planning treatment for HCC, as the presence of esophageal varices identifies patients with worse prognosis independently of the degree of liver dysfunction, etiology of liver disease, HCC stage, and treatment modality. [9,19] Moreover, the presence of clinically significant portal hypertension is associated with a 2-to 3-fold increase in the risk of mortality at 3 and 5 years after surgery for HCC, with a 3-fold increase in the risk of clinical decompensation.…”
Section: Impact Of Liver Function and Portal Hypertension On Therapeu...mentioning
confidence: 99%